Analisis Dinamika dan Keseimbangan Pembiayaan Bank Umum Syariah Dengan Pendekatan Error Correction Model - Shahmi, Mohammad Aliman; Nofrianti, Nofrianti (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The study aims to analyze the dynamics and balance of financing of Islamic Commercial Banks in Indonesia during the period 2015-2023 with a focus on changes in monetary policy, real effective exchange rate, price level, profitability, and capital adequacy. The research method uses a quantitative approach with analysis techniques using the error-correction model (ECM) approach. The results showed that monetary policy, real effective exchange rate, profitability, and capital adequacy ratio have a significant influence on the financing of Islamic Commercial Banks in Indonesia in the long run. In contrast, the price level does not show a significant influence on financing in the long run. These results explain that macroeconomic factors and banking performance are crucial in determining the balance of financing in the Islamic banking sector in Indonesia. The findings suggest that changes in monetary policy, which often reflect overall economic conditions, can affect financing decisions in Islamic banks. In addition, fluctuating real exchange rates can affect the price competitiveness and financial position of banks. Profitability, as an indicator of financial health, and the capital adequacy ratio, as an indicator of a bank's ability to bear risk, were also found to have a significant influence, suggesting that the internal performance of Islamic banks is decisive in the financing provided.